Economic stabilization : objectives, rules, and mechanisms - Egle, Walter P. (Princeton legacy library., 2015)
A theoretical discussion of the problem of achieving economic stabilization. Mr. Egle offers a commonsense compromise between those who would use only automatic devices to counteract business swings and those who would give the government great discretionary powers.Originally published in 1952.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.